Intra‐cavernous injection of BOTOX® (50 and 100 Units) for treatment of vasculogenic erectile dysfunction: Randomized controlled trial. (20th April 2021) - El‐Shaer, Waleed; Ghanem, Hussein; Diab, Tamer; Abo‐Taleb, Ahmed; kandeel, Wael
Abstract: Background: Erectile dysfunction (ED) is a socioeconomic problem.There are several options for its management including intra‐cavernosal injection (ICI). Objective: To compare the safety, efficacy, and durability of ICI of onabotulinum toxin‐A (BTX) in different doses (50 and 100 U) against placebo (saline) in the management of vasculogenic ED non‐responding to pharmacological therapy (phosphodiesterase type 5 inhibitors or/and ICI of trimix). Materials and Methods: A prospective randomized double‐blind placebo‐controlled trial was conducted between July 2016 and February 2019. A total of 176 patients were randomly assigned (1:1:1) to one of the treatment sequences: Botox 100 U group (BTX‐100; 62 patients), Botox 50 U group (BTX‐50; 59 patients), or placebo group (55 patients). All patients were followed up for 6 months. Results: Significant improvement in all parameters, that is, SHIM score & Erection Hardness Score (EHS), Sexual Encounter Profile (SEP), Global Assessment Score (GAS), and Doppler parameters ( p < 0.001) was observed in patients of BTX‐100 and BTX‐50 groups with maximum improvement at 3rd month of treatment. Around 40% of patients were responders and were able to engage in sexual intercourse. Patients in placebo group did not experience significant improvement ( p = 0.264). It was noted that at the 2nd week and 3rd months after treatment, there was no statistically significant difference in the improvement of these parameters in BTX‐100 and BTX‐50 groups ( p > 0.05). In the 6th month, there was a statistically significant difference between the aforementioned groups in favor of BTX‐100 ( p < 0.01). Conclusions: Only one‐time ICI of BTX (50 U and 100 U) is effective and safe for the treatment of refractory ED. This agent has a considerable long duration of action, particularly BTX‐100U seems to be more durable.